Assessment of the safe operation and maintenance of photovoltaic systems - Kamenopoulos, Sotiris N.; Tsoutsos, Theocharis (Energy (Oxford), 2015)
Nowadays although PVs (photovoltaics) have been a major energy source, there are limited publications focused on the risks regarding the operation and maintenance of PV systems. This subject is crucial especially by taking into account the number of additional installations due, also, to the favorable European policy. In addition, there are limited data worldwide regarding mishaps related to the operation/maintenance of installed PV. Thus, it is difficult to establish a safety policy roadmap for PV operations/maintenance projects, especially the large ones. In order to accomplish that, an operational risk management methodology is suggested to be adopted. The scope of this paper is: (i) to clarify the importance of safety at PV systems during normal operation/maintenance; (ii) to establish a baseline holistic risk assessment for installed PV working environment; (iii) to identify probable hazards incorporated to the operation/maintenance of PV systems; and (iv) to assess the associated hazards. The proposed methodology and findings should be considered as a baseline for further research in the future. •Three PV categories were identified: natural, human-made, and technological hazards.•Electricity hazards and fire fighting accumulated the highest mean scores.•The likelihood of an aviation mishap is considering at very low level.•A human-made hazard is related to vandalism/theft/sabotage.